Heat transfer performance of a finned metal foam-phase change material (FMF-PCM) system incorporating triply periodic minimal surfaces (TPMS). (May 2021) - Qureshi, Zahid Ahmed; Elnajjar, Emad; Al-Ketan, Oraib; Al-Rub, Rashid Abu; Al-Omari, Salah Burhan
Highlights: TPMS-based foams were impregnated with a phase change material. The PCM melting time decreases with TPMS foams. The average heat transfer coefficient increases with TPMS foams. Natural convection effects are more pronounced in the conventional metal foam. Abstract: Metal foams have been used extensively to enhance the thermal conductivity of phase change materials (PCMs) in thermal energy storage (TESs) systems and thermal management systems (TMSs). The conventional metal foam structure, referred to commonly as the Kelvin cell, has been characterized well and the effects of its geometric and macroscopic parameters, such as porosity, pore size, and surface area density, on the performance of metal foam–PCM composites have been investigated extensively. With the advent of additive manufacturing technology, any intricate and complex architecture can be manufactured easily, thereby opening doors for the utilization of several other candidate foams and structures in TES systems and TMSs. In this work, three triply periodic minimal surface (TPMS)-based foams (Gyroid, IWP, and Primitive) were used in a finned metal foam–PCM (FMF–PCM) system, and their heat transfer performances were compared with that of the conventional metal foam. Pure conduction and natural convection-based transient phase change simulations were performed under isothermal conditions. The results indicated that all TPMS structures exhibited enhanced heat transfer performance by reducing the melting time of the PCM and increasing the average heat transfer coefficient. Hence, TPMS-based foams offer great promise for use in TES systems and TMSs. Graphical abstract: Image, graphical abstract